Spinal cord injury due to road traffic accident in the pre-hospital phase: a grounded theory study in an Iranian context - Sepahvand, Elham; Khankeh, Hamidreza; Hosseini, Mohammadali; Akhbari, Behnam (Frontiers in Public Health, 2024)
Introduction Spinal cord injury is a devastating outcome for individuals and a major public health problem that leads to sensory, motor, and autonomic dysfunction and permanent disabilities. Thus, it is necessary to identify the causes of disability and injury both in the accident phase and in the post-accident phase. This study aimed to develop a theory based on which this complex environment can be discovered. Methods This research was a grounded theory study with the constant comparative analysis recommended by Corbin and Strauss in 2015. Participants in this study included 24 Participants were selected from Rofideh Rehabilitation Hospital and Shahid Jalaeipour Spinal Cord Injury Center of Tehran city in 2020. A semi-structured interview with an interview guide was used for data collection. Purposeful sampling method was performed within 10 months until data saturation. Lincoln and Guba’s criteria were used to assess the scientific accuracy and validity of the study. Findings The results of interviews showed that “uncertainty” was identified as the most important concern of the injured people, and “trying to save the injured” was identified as the most important concern of the witnesses and families of the injured people. The main categories included “emotional interaction,” “overwhelming anxiety,” “the scene shock,” “misunderstanding of the delay,” “inadequate emergency service,” and “insufficient understanding of the injury.” Conclusion In a traffic accident, uncertainty about the situation is the main concern of everyone at the crash scene, from pre-hospital emergency personnel, traffic police, and law enforcement officer to the patient’s companions and other witnesses. Further research is needed to shed more light on this issue.